Antibiotics: Responding to a Global Challenge - Christopher C. Butler (MDPI AG, 2012)
The miracle of antibiotics is hard to exaggerate. Each day, in every corner of the world, antibiotics improve, or could be improving outcomes in the septic neonate, the child with pneumonia, the new mother after a complicated delivery, the patient undergoing surgery, the nursing home resident with a urinary tract infection, the patient being treated of cancer, or the trauma patient on life support. The miracle also keeps our animals healthy for effective food production. But the miracle of these 'wonder drugs' is under threat and may be short lived: antimicrobial resistance is relentlessly increasing, especially for Gram negative organisms, prompting the oft expressed concern that we are plummeting head-long back into the pre-antibiotics era where clinicians and families once again will have to stand by and watch patients and loved ones die from once easily-treated infections. [...]